Family functioning, socio-economic status and adolescent’s depressive symptoms: the mediating role of hopelessness. - Rodríguez-Naranjo, María Carmen; Caño-González, Antonio (My University, 2018)
Research has shown that difficulties in family functioning contribute to developing adolescents’ depressive symptoms. Additionally, little research has been conducted in order to analyze socio-economic status (SES) differences in the relationship between family functioning and adolescent depressive symptoms. This study examined the relationships between the family variables included in the MacMaster Model of Family Functioning (MMFF), SES and depressive symptoms, as well as the mediating effects of hopelessness. Participants were 643 adolescents aged 12 to 18 years (49% male) drawn from secondary schools in Málaga (Spain). They completed the Family Assessment Device, the Beck Depression Inventory, the Beck Hopelessness Scale, and a socio-economic measure. We used conditional process analysis to test the moderation effect of gender and a dual mediation model with family functioning and hopelessness as mediators. Results showed that both family functioning as a whole and each MMFF variable, as well as SES, predicted adolescents’ depressive symptoms. In addition, gender moderated the relationship of roles assignment and behavioral control with adolescents’ depressive symptoms, which suggests the need for interventions directed to enhance family rules and boundaries, especially for boys. Finally, we found a serial mediational role of family functioning and hopelessness in the relationship between SES and depressive symptoms, suggesting that the effect of family SES on adolescents’ depressive symptoms through the development of hopelessness should also be targeted.
Keywords: Adolescentes; Depresión mental; Socio-economic status; Family functioning; Adolescent depression; Hopelessness; Gender